The Impact of Digital Marketing Campaigns in Saudi Arabia: A Social Media Sentiment Analysis Approach (Architecture Image Studies, 2025)
This present study dwells on the effectiveness of digital marketing campaigns on social networks in Saudi Arabia, focusing on user sentiment, metrics of engagement, and the role of local influencers. The research study focuses on the content of the posts from platforms such as Facebook, Instagram, Twitter, and YouTube by combining sentiment analysis, text mining, and NLP. The results show that from the sentiments, engagement is highly positively correlated; hence, posts that trigger positive emotions have drastically higher interaction rates. Facebook and Instagram are the most engaging channels, while Twitter presented more critical sentiment that requires another way of engaging. This analysis has identified Saudi influencers and the cultural aspect as very important in setting the success of any campaign. On the other hand, the posts of local influencers were more positive in sentiment and ensured higher engagement, indicating the importance of culturally relevant marketing. Temporal engagement, however, was different over time, reaching its peak on events such as the launch of a product and promotion by an influencer. The study concludes that the brands targeting Saudi audiences should employ content most likely to yield positive sentiment, partner with local influencers, and monitor the campaign performance in real time to maximize engagement and guarantee success.